Pengaruh Media Permainan Interaktif Berbasis Digital (Kahoot) Terhadap Hasil Belajar Kognitif Siswa Pada Materi Ipas Kelas IV Sekolah Dasar Negeri Karangduak 1 - Alviansyah, David; Nailah, Faiqatun; Azizah, Nur; Akbar, Faishal; Hardiansyah, FramzHardiansyah (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE EFFECT OF DIGITAL-BASED INTERACTIVE GAME MEDIA (KAHOOT) ON STUDENTS' COGNITIVE LEARNING OUTCOMES IN IPAS MATERIAL FOR FOURTH-GRADE STUDENTS OF SDN KARANGDUWAK 1 This study aims to analyze the effect of using the Kahoot-based interactive digital game media on students’ learning outcomes in the Science and Social Studies (IPAS) subject for fourth-grade students at SDN Karangduak 1. The background of this research arises from the low level of student engagement and motivation in the learning process, which is still dominated by conventional methods. This research employed a quantitative approach with a quasi-experimental design, using the pretest–posttest control group design model. The subjects consisted of two classes: the experimental class using Kahoot and the control class applying the lecture method. Learning outcome data were collected through multiple-choice tests administered before and after the treatment and analyzed using normality testing and an Independent Sample t-test. The results revealed a significant difference between the average scores of students in the experimental and control groups, with a significance value of 0.000 0.05. This finding indicates that the use of Kahoot effectively improves students’ learning outcomes. Interactive digital game media such as Kahoot have been proven to create an active, enjoyable, and collaborative learning atmosphere while increasing students’ motivation and concentration throughout the learning process.